Robot-like dexterity without computers and motors: a review of hand-held laparoscopic instruments with wrist-like tip articulation. (2nd July 2016) - Anderson, Patrick L.; Lathrop, Ray A.; Webster III, Robert J.
ABSTRACT: Introduction: Conventional manual laparoscopic instruments for minimally invasive surgery have limited dexterity within the patient, making procedures challenging. Surgical robotic systems offer enhanced articulation, but at substantial financial costs. This has motivated the development of high-dexterity, low-cost laparoscopic instruments. Areas covered: This article reviews both commercial and academic results on creating fully mechanical (i.e. non-robotic) laparoscopic instruments that provide wrists or wrist-like dexterity within the patient. We review the state of the art in the development of these mechanical instruments, focusing on the surgeon interface, wrist mechanism, and the kinematic mapping between the two. Expert commentary: Current articulated mechanical laparoscopic instruments exhibit a wide range of designs, with no clear consensus on what makes such devices easy to use. As these technologies mature, user studies are needed to determine surgeon preferences. Articulated, low-cost instruments have the potential to impact the minimally invasive surgery market if they provide compelling benefits to surgeons.